2018
DOI: 10.1259/bjr.20180270
|View full text |Cite
|
Sign up to set email alerts
|

Automation in intensity modulated radiotherapy treatment planning—a review of recent innovations

Abstract: Radiotherapy treatment planning of complex radiotherapy techniques, such as intensity modulated radiotherapy and volumetric modulated arc therapy, is a resource-intensive process requiring a high level of treatment planner intervention to ensure high plan quality. This can lead to variability in the quality of treatment plans and the efficiency in which plans are produced, depending on the skills and experience of the operator and available planning time. Within the last few years, there has been significant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
195
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(202 citation statements)
references
References 210 publications
(245 reference statements)
2
195
0
5
Order By: Relevance
“…However, what can be ascertained is that results from this study, which demonstrate that automated planning is non-inferior to expert manual planning, are consistent with existing literature and supportive of Pareto navigation guided automated planning. Furthermore, in a recent review on automated planning by Hussein et al [37] only two out of the 81 identified evaluative studies were for complex pelvis treatments (SIB technique with nodal irradiation) [8,38]. Our work builds on this limited evidence base, providing further data in support of automation for even the most complex tumour sites.…”
Section: Discussionmentioning
confidence: 80%
“…However, what can be ascertained is that results from this study, which demonstrate that automated planning is non-inferior to expert manual planning, are consistent with existing literature and supportive of Pareto navigation guided automated planning. Furthermore, in a recent review on automated planning by Hussein et al [37] only two out of the 81 identified evaluative studies were for complex pelvis treatments (SIB technique with nodal irradiation) [8,38]. Our work builds on this limited evidence base, providing further data in support of automation for even the most complex tumour sites.…”
Section: Discussionmentioning
confidence: 80%
“…These treatment plans may therefore not reflect treatment plans produced in clinical practice, as less detailed feedback or discussion of treatment plans is possible and plans may therefore be suboptimal. Automated treatment planning techniques, for example knowledge-based treatment planning, protocolbased automatic iterative optimization or multicriteria optimization, could be used to determine whether a treatment plan can be further optimized [14].…”
Section: Discussionmentioning
confidence: 99%
“…Artificial intelligence (AI) techniques will rapidly find relevant and extensive applications in radiotherapy (Thompson et al, 2018). An important example is the ability of AI in supporting planners to generate automated solutions for treatment planning optimization that are integrating (in part replacing) and improving the traditional, manually optimized, planning (Hussein et al, 2018). AI is also particularly promising to support online treatment planning and adaptive radiotherapy (Boon et al, 2018).…”
Section: Artificial Intelligence and Big Datamentioning
confidence: 99%